Effect of Extraction Methods on Physical and Chemical Properties of Pectin from Overripe 'Namwa' Banana - Ji-u , Phornpan; Neamsorn, Natawut (Journal of Food Technology, Siam University, 2022)
This research studied on the pectin extraction from three parts of overripe ‘Namwa’ banana i.e., peel, pulp and whole fruit with 2 extraction methods. The first method was done by using 0.05 M hydrochloric acid (HCl) at 95°C, 60 min and substrate to extractant ratio of 1:12. The second method was carried out by using 0.05 M citric acid and substrate to extractant ratio of 1:20 at 121 °C for 180 min. The results showed that pectin from both acid extractions had brown color. The yield and chemical properties of pectin (equivalent weight, methoxyl content, degree of esterification and galacturonic acid content) extracted by HCl were significantly higher than by citric acid. The highest yield of HCl-pectin extracted obtained from pulp (15.23% d.b.) while the HCl-pectin extracted yield from whole fruit and peel were 9.38% d.b. and 2.49% d.b., respectively. The pectin extracted from three parts of overripe ‘Namwa’ banana were high-methoxyl pectin due to the methoxyl contents and the degree of esterification of pectin extracted which were in range of 11.60-15.49% and 82.74-93.84%, respectively. The galacturonic acid contents of pectin in this research were in range of 43.81-53.18%.